ARTIST IMAGE AS A POLITICAL TOOL IN THE PAN ELECTORAL STRATEGY FOR THE 2024 ELECTIONS: A CASE STUDY OF UYA KUYA - Vallerian Antaresa; Ahmad Zaidan Zidna Fann; Alexza Courientdya Nugroho Putrie; Chayara Alima; David Jonathan; Gabriella Priscilla Napitupulu; Khanza Azzahwa; Muhammad Putra Tyanto; Abdul Ghofur (Ikatan Dosen Menulis, 2026)
This study aims to analyze how Uya Kuya’s personal branding strategy was integrated into the National Mandate Party’s (PAN) political marketing strategy during the 2024 election campaign and to explain the impact of utilizing public figures on PAN’s vote share. This study employs Brian McNair’s (2011) Political Communication Theory and Cross, Katz, and Pruysers’ (2018) Political Personalization Theory. The methodology used is descriptive qualitative research with a postpositivist approach. Data were obtained through a documentary study of online news, official party documents, social media content, General Election Commission (KPU) data, and prior research. The results indicate that PAN integrated Uya Kuya’s popularity, digital follower base, and advocacy track record into its political marketing strategy through sonic branding, audiovisual campaigns, social media, and face-to-face campaigns. This strategy successfully converted the celebrity’s symbolic capital into significant electoral support, as evidenced by Uya Kuya’s 81,463 votes in the DKI Jakarta II electoral district and his contribution to the increase in PAN’s national vote share from 6.84 percent in the 2019 election to 7.23 percent in the 2024 election. This study concludes that the image of an artist functions as an effective political instrument in boosting a party’s electability through political personalization and integrated political communication.